SENGKETA HUKUM DALAM KONTRAK KONSTRUKSI: STUDI BANDING SISTEM HUKUM PERDATA - Sami'an, Sami'an; Rosyadi, Imron; Suliyanto, Eko; Soeharto, Achmad; Aulia, Aulia (Gapenas Publisher, 2024)
The manufacture of construction services is based on the values of honesty and justice, profit, equality, harmony, balance, professionalism, independence, openness, partnership, safety, freedom, sustainable development, and environmental insight. A phenomenon every day. The problem in the implementation of construction work in Indonesia is that the construction takes place between service users and contractors as service providers. This risk is intertwined because construction contracts are dynamic and different from other contracts. This research is based on normative law. Procedures for systematic understanding and grammatical understanding of all legal norms and legal materials related to research are used in the analysis of legal materials. The results of the research show that the Law Number. For Construction Services 2/2017, construction bids are completed first by thinking about reaching the convention, and if the parties to the dispute do not reach the convention, until the arrangement is tried through the stages of arrangement stipulated in the construction contract. Keywords: Legal Dispute Resolution, Construction Contract